2018
DOI: 10.3389/fpsyg.2018.01440
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Relationships of Playfulness With Indicators of Health, Activity, and Physical Fitness

Abstract: Adult playfulness is a personality trait that enables people to frame or reframe everyday situations in such a way that they experience them as entertaining, intellectually stimulating, or personally interesting. Earlier research supports the notion that playfulness is associated with the pursuit of an active way of life. While playful children are typically described as being active, only limited knowledge exists on whether playfulness in adults is also associated with physical activity. Additionally, existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 82 publications
(130 reference statements)
4
58
0
3
Order By: Relevance
“…. to ease tense situations or cheer other people up” (Proyer et al, 2018, p. 2). In the present study, playful behavior was linked to relationships on the PERMA-Profiler scale, indicating that being playful when socializing may enhance connections.…”
Section: Discussionmentioning
confidence: 99%
“…. to ease tense situations or cheer other people up” (Proyer et al, 2018, p. 2). In the present study, playful behavior was linked to relationships on the PERMA-Profiler scale, indicating that being playful when socializing may enhance connections.…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism behind the longitudinal association between mental wellbeing and LTPA is personality, which is closely related not only to mental well-being (Kokko et al 2015;Steel et al 2008) but also to LTPA (Rhodes and Smith 2006). For example, the personality traits of playfulness (Proyer et al 2018) and activity (facet of extraversion) (Rhodes et al 2002;Røysamb et al 2018) are linked to both mental wellbeing and LTPA. Like mental well-being (Kokko et al 2013a), personality has high rank-order stability in adulthood (Rantanen et al 2007;Roberts and DelVecchio 2000); this might explain why LTPA did not predict mental well-being in this study but vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Play is physiologically relevant due to its positive effect on cardiovascular health, keeping those partaking healthy throughout their lives. Indeed, Proyer et al observed that playfulness positively correlated with cardiorespiratory fitness and specific health behaviours (Proyer, Gander, Bertenshaw, & Brauer, 2018). In addition, it has been more commonly accepted that play, at least in mammals, can be used as both physical and mental training or preparation for the unexpected (Spinka, Newberry, & Bekoff, 2001).…”
Section: Physical and Mental Resiliencementioning
confidence: 99%